High electrochemical performance and structural stability of CoO nanosheets/CoO film as self-supported anodes for lithium-ion batteries. Issue 4 (15th February 2021) - Wang, Lin-Hui; Teng, Xiao-Ling; Qin, Yu-Feng; Li, Qiang
Abstract: The traditional methods to prepare electrodes of lithium-ion batteries need to add binders which reduce the capacity of electrode materials. In this work, CoO nanosheets/CoO film as self-supported anodes were designed and prepared. The CoO nanosheets/CoO film exhibited better electrochemical performance and structural stability than CoO nanosheets directly grown on copper foil and most previous CoO-based electrode materials. The CoO film prepared by magnetron sputtering firmly fixed the nanosheets prepared by the hydrothermal method on the film. The buffer layer of CoO film can prevent CoO nanosheets from crushing and falling off, thus greatly improving the electrochemical performance of this kind of material. The CoO nanosheets/CoO film has great potential applications in lithium-ion batteries.